Uma experiência de atendimento escolar para criança com Transtorno do Espectro Autista (TEA) - SOUZA, Lorrany Francisca de (Universidade Federal do Tocantins, 2021)
This study aimed to investigate the characteristics of the inclusion process of students with ASD (Autistic Spectrum Disorder) in a public elementary school. In this study, we seek to analyze whether teachers are prepared to care for children with ASD, taking into account the current scenario of the educational system that guides educational actions towards a student inclusion process. We adopted the qualitative research and the case study, having as instruments: the observation made through the registration in a field diary and the application of a questionnaire for the subjects participating in the research: students with ASD, teachers and caregiver / support teacher. The results obtained in the research show that the specialization and training of teachers in the areas of Special Education is essential, the lack of knowledge on the part of teachers provides an increase in the teaching gap and ends up harming the educational development of students with ASD.